2007
DOI: 10.1039/b708310f
|View full text |Cite
|
Sign up to set email alerts
|

Slice imaging of the photodissociation of acetaldehyde at 248 nm. Evidence of a roaming mechanism

Abstract: The photodissociation of acetaldehyde in the molecular channel yielding CO and CH(4) at 248 nm has been studied, probing different rotational states of the CO(nu = 0) fragment by slice ion imaging using a 2+1 REMPI scheme at around 230 nm. From the slice images, clear evidence of the co-existence of two different mechanisms has been obtained. One of the mechanisms is consistent with the well-studied conventional transition state in which CO products appear rotationally excited, and the second is consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
98
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 16 publications
(28 reference statements)
8
98
1
Order By: Relevance
“…A preliminary quasiclassical trajectory (QCT) study by Shepler et al (14) indicated that trajectories initiated from the conventional TS (representing exclusively the conventional TS pathway) produced a CO rotational distribution much hotter than experiment, whereas the distribution obtained from trajectories initiated from the equilibrium CH 3 CHO geometry are in good agreement with the HK experiment. More recent experiments at 248 nm suggested a greater contribution to the CH 4 ϩ CO roaming channel (12), although at this energy more than one pathway can lead to formation of CO, making interpretation of the experiment potentially ambiguous.…”
mentioning
confidence: 99%
“…A preliminary quasiclassical trajectory (QCT) study by Shepler et al (14) indicated that trajectories initiated from the conventional TS (representing exclusively the conventional TS pathway) produced a CO rotational distribution much hotter than experiment, whereas the distribution obtained from trajectories initiated from the equilibrium CH 3 CHO geometry are in good agreement with the HK experiment. More recent experiments at 248 nm suggested a greater contribution to the CH 4 ϩ CO roaming channel (12), although at this energy more than one pathway can lead to formation of CO, making interpretation of the experiment potentially ambiguous.…”
mentioning
confidence: 99%
“…The branching to each pathway obtained herein is averaged over all the J levels, similar to that by Lee et al based on integration of all rotational states, 4 but different from most J-dependence results by using ion imaging method. 2,7,8,14 Note that the low-J component for CH 3 CHO photolyzed at 308 nm is free from interference by triple fragmentation (CH 3 + CO + H). 15 The HCO obtained even at 266 nm may not undergo secondary decomposition.…”
mentioning
confidence: 99%
“…In addition, an alternative roaming pathway is initiated from the barrierless radical products (HCO + CH 3 ) on the ground state surface. [4][5][6][7][8] The incipient radicals meander with slow motion around varied configuration spaces in the weak attractive field of the moieties and ultimately undergo intramolecular abstraction to form the same molecular products.…”
mentioning
confidence: 99%
“…12 Trajectory calculations initiated at the S0 TS leads to rotationally excited CO products and partitioning of a large fraction of the available energy into translational recoil, in agreement qualitative with the experimental 5 observations. 13,14 Acetaldehyde was the second molecule to show evidence of photochemical roaming, with the observation of low-J CO formed in conjunction with highly internally excited CH4, [15][16][17][18] consistent with the dynamical signatures established for roaming in formaldehyde. [19][20][21] Quasiclassical trajectory calculations on ab initio potential surfaces supported this interpretation and indicated that roaming involved frustrated dissociation and subsequent intramolecular reaction between the CH3 + HCO radical products.…”
Section: Introductionmentioning
confidence: 97%
“…Ion imaging measurements have also detecting H atoms directly. 16 In this paper, we report a study of acetaldehyde photochemistry following excitation at wavelengths between 265-328 nm. Ion imaging experiments using single-photon VUV ionization of CH3 radicals show three distinct competitive photochemical mechanisms.…”
Section: Introductionmentioning
confidence: 99%